The Degree of Application of Teachers of the Higher Basic Stage in Zarqa Governorate to Alternative Evaluation Strategies in Distance Education during the Corona Pandemic - Ayman Mohammad Khalaf Oliemat; Maha slama Algwari; Shifa Sulieman Farhan Almashaqba (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: This study aimed to reveal the degree to which teachers of the higher basic stage apply alternative assessment strategies in the first Zarqa Education Directorate in distance education during the Corona pandemic, according to the enrollment variable in professional development programs. Methods: The study followed the descriptive approach to achieve its goal. A questionnaire was prepared to collect data, and its validity and reliability were confirmed, as it was applied to (273) male and female teachers of the upper basic stage in the first Zarqa Education Directorate were chosen randomly. Results: The results showed that teachers of the higher basic stage in the first Zarqa Education Directorate apply alternative evaluation strategies in a low degree (M=2.41). Also, there are no statistically significant differences between the means of degrees of their application of alternative evaluation strategies, according to the variable of enrollment in professional development courses. Conclusions: The study concluded that possessing alternative assessment strategies through training courses does not necessarily mean applying them in teaching practices. Because enrollment in training courses and possession of knowledge in pedagogy may be in order to succeed in the training course for the purposes of career advancement, according to the rank system for teachers, which entails moving from one rank to another to succeed in these courses. Also, enrollment in training courses needs to follow up on the transmission of its impact on the teaching practices of teachers.